The Sage Handbook of Nations and Nationalism - Gerard Delanty, Krishan Kumar (Sage Publications, 2006)
The persistence - some would say: revival - of nationalism across the recent history of modernity.. has taken manu scholars in the social science bu surprise. In response, interest in the analysis of nationalism has increased and given rise to a great variety of new angles under which to study the phenomenon. what was missing in the cacophony of voices addresing nationalism was a volume that brought them together and confronted them with each other.